DEVELOPMENT OF NANOSTRUCTURE BASED ORGANO-METAL HALIDE PEROVSKITE SOLAR CELLS - Daniyar, Bayan (Nazarbayev University School of Engineering and Digital Sciences, 2021)
Organometal halide perovskite solar cells have engaged researchers' consideration because of their obtained efficiencies in comparison with conventional photovoltaic cells. The aim of this thesis is to investigate the performance of perovskite solar cells (PSCs) after applying the SnO2 nanorods grown on different seed layers as electron transport layers (ETLs). The strategy is to apply vertically aligned nanorods that are grown via the hydrothermal method on ETL to reach a high PSC performance. In this study, organometal halide perovskite-based PSCs with the incorporation of SnO2 nanostructures on seed and compact layers were prepared and characterized. In order to optimize SnO2 nanorod arrays (NAs) many experiments were provided by changing the volume of acetic acid and the growth time. The impact of seed and compact layer on NAs were investigated. The seed layers were prepared by radiofrequency (RF) Magnetron Sputtering and SnO2 quantum dots, and nanoparticles were prepared by the spin-coating method. The grown nanorods on the seed layer showed directional growth than without the seed layer. The photovoltaic performance of PSCs, spectroscopic analysis, X-ray diffraction, and images from scanning electron microscopy (SEM) have been presented. The characterization techniques are used to assess the morphology and quality of NRs, the device performance. The obtained PSC based on SnO2-NAs demonstrated a PCE of 14.2 % with Voc 0.99 V, Jsc of 24.8 mA/cm2, and FF - 58 %. The growth of NRs is rised with growth time 24h by 1.7 from 137.3 nm to 234.3 nm, after applying the replacement of substrate into the new prepared solution after 12 h. With the increased amount of acetic acid, the nanorods are less dense and resolved from one another.
Keywords: Type of access: Gated Access; Research Subject Categories::TECHNOLOGY; perovskite solar cells; PSCs; nanostructure; SnO2 nanorods